USE OF WOOL FABRICS, CLASSIFICATION AND CODING OF WOOL FABRICS - O.A.Toshbekov; PhD M.K. Urozov; I.B. Boltayeva; M.F. Hamrayeva. (Scholar Express Journals, 2022)
Today, the processing of textile waste in the world is determined by the steady expansion of the demand for textile fibers, the demand for raw materials for their production. For the production of such products are mainly used fine wool of sheep. The coarse wool of sheep is usually discarded after shearing. Because until now, there was no technology to process it
Keywords: Wool; fabrics; coarse; products